Pengaruh Pelatihan Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Dengan Lingkungan Kerja Sebagai Variabel Intervening - Rahmat, Jajang; Ahmadi, Slamet; Widyastuti, Titing; Gunawan, Y.I. (GEMA EKONOMI, 2023)
Training, motivation, and discipline are Three factors that are thought to be relatively large in influencing the performance of employees at PT. Unlock Main Techniques. to prove the influence of the three, and this research was conducted with the aim of knowing the effect of Training, Motivation, and Discipline on the work environment as an interference at PT. Main Bukaka Engineering Tbk. This research was conducted at PT Bukaka Teknik Utama Tbk. Located on Jl. Raya Narogong. took 84 students as a research sample, calculated using the Slovin Formula from a total population of 630 employees at 10% margin error. Data was collected using an online questionnaire instrument with five rating scales from strongly disagree to agree strongly. The research was conducted by analyzing data assisted by statistics (SPSS Version 25). Quantitative, namely by describing research data and conducting inference analysis. Instrument variables include validity and reliability tests as well as classical assumption tests. Multiple linear regression analysis methods is used as an analysis tool while the hypothesis is made by t-test and F-test. The research yielded two main findings per the proposed hypothesis: 1) Training has an effect on employee performance 2) Motivation has an effect on Voting Decisions 3) Discipline influences impressions on employee performance. Based on these findings, it is recommended that efforts be made to improve Training, Motivation, Discipline, and Employee Performance to improve Voting Decisions